ASSESSMENT OF LIFE HISTORY TRAITS OF CHANNA MARULIUS FOR FISHERY MANAGEMENT IN PAKISTAN - D. Guilin; M. Mohsin; M. Noman; S. A. Raza; A. Mehak (Journal of Animal and Plant Sciences, 2019)
This is the first attempt to investigate growth and mortality parameters of Channa marulius (Hamilton, 1822), a major murrel species, caught from the Indus River, Pakistan. Six research surveys were conducted at Chasma Barrage, located on the Indus River, during the months May-October, 2016. Length-weight and length frequency readings, n = 674, were collected and evaluated by using FiSAT II computer application. The observed length and weight ranged between 5-39 cm and 1-301 g correspondingly. The estimated values of b, a and R2 remained 3.033, 0.006 and 0.987 respectively. Growth parameters, L∞ = 40.95 and K = 0.3 year-1, were evaluated by applying ELEFAN I routine via von Bertalanffy growth equation. The computed values, by employing LCCC, of Z, M, F and E remained 1.18 year-1, 0.68 year-1, 0.5 year-1 and 0.42 year-1 in that order. YPRA indicated that when tc = 1, estimated values of Fmax, F0.1 and Fcurrent were 0.9 year-1, 0.75 year-1 and 0.50 year-1 correspondingly. LSVPA indicated the highest mortality rates were in the 29-32 cm length cohort. The lower value of Fcurrent, 0.50 year-1, than Gulland BRP, M = Fopt = 0.68 year-1, suggests that this fishery resource is in a safe condition.
Keywords: growth; mortality; Channa marulius; Indus River; Pakistan